A simple method to obtain ursolic acid - Ludeña, M.A.; Tupa-Quispe, A.L.; Huamán Quispe, R.I.; Serrano Flores, C.A.; Robles Caycho, J. (Elsevier, 2021)
A simple method has been developed to obtain ursolic acid (UA) by crystallization and recrystallization of the ethanol extract of Clinopodium revolutum. Its structure was confirmed by 1D (1H-, 13C-, DEPT 45, 90 and 135) and 2D (COSY, HMBC and HSQC) nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared spectroscopy (FT-IR). The results provide a theoretical basis for considering the species Clinopodium revolutum with a source of UA.
Keywords: Ursolic acid; Clinopodium revolutum; NMR spectroscopy; https://purl.org/pe-repo/ocde/ford#1.04.02